2020
DOI: 10.1038/s41598-020-64372-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intradialytic versus home-based exercise programs on physical functioning, physical activity level, adherence, and health-related quality of life: pilot study

Abstract: Intradialytic exercise (ID) programs are effective and safe for hemodialysis (HD) patients to avoid functional deterioration. However, exercise is not routinely undertaken in most HD units, and we do not know if home-based (HB) programs are as effective as ID programs. The purpose of this study was to compare the effects of 16 weeks of ID exercise versus a HB exercise program for HD patients. A total of 46 patients were randomly assigned to the ID group (n = 24) or HB group (n = 22). They completed a 16-week c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 49 publications
4
32
0
Order By: Relevance
“…There was no change in the HRQoL score. Physical activity levels and physical function changed similarly in response to both treatments [96]. As a result, the effectiveness of IDE and HBE is comparable, and both produce positive effects.…”
Section: Analyses Of Intradialytic Vs Non-clinical Exercise Programmesmentioning
confidence: 80%
“…There was no change in the HRQoL score. Physical activity levels and physical function changed similarly in response to both treatments [96]. As a result, the effectiveness of IDE and HBE is comparable, and both produce positive effects.…”
Section: Analyses Of Intradialytic Vs Non-clinical Exercise Programmesmentioning
confidence: 80%
“…Ortega-Pérez de Villar et al (2020) assessed the level of depression using the CES-D scale. The effect size of CES-D change between baseline and post-intervention was not significant for the group participating in home-based exercises; however, the effect size was medium ( d = 0.52) for the group participating in exercise in a dialysis unit.…”
Section: Resultsmentioning
confidence: 99%
“…There are several studies comprising 46–60 patients comparing ID with interdialytic in-centre or home-based training, with observation periods ranging from 4 to 6 months. Two of the studies found positive effects of exercise training on aerobic capacity in all groups [ 43 , 44 ]; one study found no effect [ 45 ].…”
Section: Where and When To Exercise?mentioning
confidence: 99%
“…In some studies, the number of screening failures, defined as patients declining participation due to a lack of interest, equals or exceeds the number of randomized patients [ 54–56 , 58 , 60 ]. However, there are a considerable number of studies with patients on dialysis as well as with NDD CKD characterized by a relatively high percentage of randomized patients compared with screened patients/source population and a low number of screening failures [ 17 , 34 , 35 , 37 , 38 , 43 , 44 , 52 , 53 , 57 , 61 , 64 , 65 ].…”
Section: Participation and Adherencementioning
confidence: 99%